High order explicit hybrid methods for solving second-order ordinary differential equations (Kaedah hibrid tak tersirat peringkat tinggi bagi menyelesaikan persamaan pembezaan biasa peringkat-dua) - Samat, F; Ismail, F; Suleiman, M (Universiti Kebangsaan Malaysia, 2012)
Two explicit hybrid methods with algebraic order seven for the numerical integration of second-order ordinary differential equations of the form y̋ = f (x, y) are developed. The algebraic order of these methods is the highest in comparison with other explicit hybrid methods of the same class. Numerical comparisons carried out show the advantage of the new methods